Comparative Study Between Outcome of Holmium: Yag Laser And Pneumatic Lithotripsy for Mid and Lower Ureteric Calculus (Bangladesh Journal of Urology, 2025)
Background: Ureteric calculus is among the most common disorders in the urological field. Miniaturization of endoscopic devices in urology has revolutionized the management of ureteric calculi. Different energy sources can be used for ureteroscopic stone fragmentation, such as pneumatic, ultrasonic, laser or electrohydraulic. Semi-rigid ureteroscope is effectively used to manipulate mid and lower ureteric calculus.Objective: To compare the outcome between Holmium: Yttrium Aluminum Garnet (Ho: YAG) laser and pneumatic lithotripsy for mid and lower ureteric calculus.Methods: This prospective study was carried out at National Institute of Kidney Diseases and Urology (NIKDU), Dhaka from January 2020 to June 2021. Sixty four patients were selected by purposive sampling technique and allocated into two groups as LL group (Laser lithotripsy group) and PL group (Pneumatic lithotripsy group) by lottery. Comparison was done on the basis of stone clearance rate, operation time, per operative stone migration and ureteral mucosal injury, post operative hematuria and fever, duration of post operative hospital stay. Test of significance was independent sample t-test for quantitative outcome and Chi-square (X2) test or Fisher’s exact test for categorical outcome. 95% confidence interval was used. p value of less than 0.05 was considered significant.Results: Mean age was 39.5+13.08 years in group LL and 38.47+10.28 years in group PL (p=0.145). Mean stone diameter was 9.83+2.07 mm and 10.48+2.3 mm in LL and PL group respectively with no statistically significant difference (p=0.468). In LL group 20% patient had mid ureteric calculus and rest in lower one. In PL group, 26.66% and 73.33% patient had mid and lower ureteric calculi respectively. Mean operation time was calculated as 38.13+5.94 minutes in LL group and 40.17+3.59 minutes in PL group with no significant difference (p=0.11). After 1st month of ureteroscopy, stone clearance of LL group (83.33%) was found significantly high (p=0.04) compared to PL group (60%), while after 3rd month, stone clearance of both groups (96.66% vs. 90%) was found statistically similar (p=0.61). In both group there were no statistical difference in aspect of mucosal injury (p=0.70), stone migration (p=0.612) and postoperative fever (p=0.31). A statistically significant more postoperative hematuria (p=0.02) were found in PL group. Mean duration of postoperative hospital stay was significantly short in LL group than PL group (36.83+9.92 vs 47+14.46; p=0.002).Conclusion: In this study, Ho: YAG laser had advantages of a higher stone clearance rate in the early postoperative period than pneumatic lithotripsy with similar success rate in late postoperative period. Post operative gross hematuria and hospital stay were significantly high in PL group.Bangladesh J. Urol. 2024; 27(1): 5-10